2022
DOI: 10.1177/03611981221088583
|View full text |Cite
|
Sign up to set email alerts
|

Surface Characteristics of Ageing Asphalt Binder Coupling Thermal Oxidation and Ultraviolet Radiation

Abstract: In this study, styrene-butadiene-styrene (SBS) modified asphalt binder was aged by thermal oxidation coupled with ultraviolet (UV) radiation. Fluorescence microscopy (FM), scanning electron microscopy (SEM) with energy dispersive x-ray (EDX) detector, surface free energy, optical technology, Fourier transform infrared spectroscopy, and dynamic shear rheometer were used to explore the surface characteristics and trace the chemo-rheological evolution of the asphalt binder at various durations of aging. Both FM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Compared with the continuous yellow-green fluorescence in modified asphalt, the SBS content in aged SBS-modified asphalt has been reduced to a very low level, and the number of SBS modifiers after aging has been greatly reduced. It can be inferred that the SBS triblock copolymer underwent severe chain scission after asphalt aging, which is consistent with the findings of previous studies ( 2731 ). As shown in Figure 5 c , the SBS particulates in regenerated SBS-modified asphalt are significantly restored, and the distribution is closer to that of the original SBS-modified asphalt, where the SBS particulates are basically restored to the level when they were not aged.…”
Section: Study Of the Microscopic Characteristics Of Rejuvenationsupporting
confidence: 92%
See 1 more Smart Citation
“…Compared with the continuous yellow-green fluorescence in modified asphalt, the SBS content in aged SBS-modified asphalt has been reduced to a very low level, and the number of SBS modifiers after aging has been greatly reduced. It can be inferred that the SBS triblock copolymer underwent severe chain scission after asphalt aging, which is consistent with the findings of previous studies ( 2731 ). As shown in Figure 5 c , the SBS particulates in regenerated SBS-modified asphalt are significantly restored, and the distribution is closer to that of the original SBS-modified asphalt, where the SBS particulates are basically restored to the level when they were not aged.…”
Section: Study Of the Microscopic Characteristics Of Rejuvenationsupporting
confidence: 92%
“…The aging process of styrene-butadiene-styrene (SBS)modified asphalt involves both the aging of the matrix asphalt and the degradation of the SBS modifier, in which the oxidative degradation of the SBS modifier is an essential factor leading to the deterioration of modified asphalt performance (27)(28)(29)(30)(31). While the physical properties of SBS-aged asphalt can be improved to some extent by waste soybean oil, degraded SBS modifiers cannot be restored.…”
mentioning
confidence: 99%
“…where Pa is air void in the asphalt mixture (%), Va is the void volume of the asphalt mixture (cm 3 ), E is the sample volume (cm 3 ), B is the weight of the saturated sample with a dry surface after saturating the sample with a vacuum pump (gr), and S is the sample saturation percentage (%). The samples were saturated and then transferred to an isolated plastic bag.…”
Section: Aging Test Of Bitumen and Asphaltmentioning
confidence: 99%
“…The thermaloxidative aging of bitumen occurs from the mixing stage to the end of pavement life. There are two phases for the thermal-oxidative aging of bitumen: one is short-term aging and the other is long-term aging [3]. Short-term aging occurs during asphalt mixture construction, while long-term aging happens during the pavement's service life.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them are added to modifed asphalt to enhance its performance. Tere are relatively many studies on adding certain kinds of antiultraviolet additives to modifed asphalt to enhance its anti-ultraviolet ability, and there are many kinds of additives currently used to achieve the UV ageing resistance performance of asphalt [7,8]. Te study found that the addition of 0.8% carbon black can maximize the antirutting factor of asphalt [9,10].…”
Section: Introductionmentioning
confidence: 99%